Konsentrasi Silika (Si) Dalam Debu Jatuh Di Area Pabrik Pengolahan Kelapa Sawit PT. Z - Annisah Muslimah; Hafidawati Hafidawati; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
PT. Z is the palm oil processing mill that utilizes solid waste of palm shells and fiber as boiler fuel. This process will produce particulate emissions, one of which is dustfall which contains Silica (Si) because more than 50% of the constituent elements of boiler are Silica. Dustfall sampling implemented by using dustfall collector based on SNI 13-4703-1998, for the calculation of silica concentration is based on Atomic Absorption Spectrofotometry result. The result indicated that Silica concentration at several points had exceeded the threshold value from Per.13/Men/X/2011 which is 10 mg/m3 with the amount of result is 9,75 – 11,47 mg/m3. This is due to the location of fiber collection which is not far from the sampling location.Keywords: Dustfall, palm oil mill, silica